Contribution of Penja Pepper Production on Economic Well-Being in Cameroon - Mbu Daniel Tambi (Agricultural Science, 2020)
Improving household well-being by intensifying agricultural production is a major concern of most developing countries. Our main objective is to quantify the contribution of Cameroon Penja pepper production on economic well-being. With the used of multiple correspondence analyses we constructed a well-being indicator using primary data collected among pepper producers and the result is estimated using ordinary least square. The results show that Penja pepper production is significantly corroborating with household economic well-being. The result is explained by industrial pepper production, while climate change, financing difficulties and availability of cultivated land are the main constraints faced by Penja pepper farmers. Decision makers should create policies to regulate the pepper market in terms of exportation of the crop. This is a wise step towards increase household economic well-being.